O-010 Stent assisted coiling versus coiling of unruptured intracranial aneurysms in the MAPS trial: safety, efficacy, and mid term outcomes. (4th July 2012) - Hetts, S; Turk, A; English, J; Mocco, J; Prestigiacomo, C; Nesbit, G; Ge, S; Jin, J; Murayama, Y; Gholkar, A; Barnwell, S; Lopes, D; et al.
Abstract : Background and Purpose: Prior studies have reported that stent-assisted coiling (SAC) may result in less aneurysm recanalization but more complications than coiling alone (CA). We evaluated outcomes of SAC in the prospective, multi-center MAPS Trial. Materials and Methods: 361 MAPS patients with unruptured intracranial aneurysms (UIA) were treated per protocol by SAC or CA. Data were analyzed post hoc for all UIAs and for the wide neck (≥4 mm) aneurysm (WNA) subset. Baseline patient and aneurysm characteristics, procedural details, neurological outcomes, and safety data were compared. An independent core laboratory evaluated all angiographic outcomes. Groups were not randomized to SAC or CA and are dissimilar, especially within the large UIA group. Results: Baseline characteristics. 137 of 361 patients received a Neuroform stent. SAC patients were more likely to be North American (88% vs 66%, p<0.0001). Cardiovascular disease (≥2 CAD risk factors) was more common in the SAC group but did not reach statistical significance. Otherwise, baseline demographics were similar. Aneurysm characteristics. Among UIAs, 62% of SAC vs 33% of CA were WNA, (p<0.0001) and the dome-to-neck ratio was lower for SAC (1.5 vs 2.1, p<0.0001). Among WNAs, more CA aneurysms had domes >10 mm (48% vs 31%, p=0.03), while SAC aneurysms had lower dome-to-neck ratios (1.5 vs 1.9, p<0.0001). Procedural characteristics. For UIAs, packing density trended higher with SAC (26.2% vs 24.2%, p=0.07). Among WNAs, SAC packing density was significantly higher than CA (26.4% vs 21.1% p=0.002). Periprocedural significant adverse events (SAEs) were not different between SAC and CA (6.6% vs 4.5%, p=0.39). Neurological outcomes and safety. At 1 year, SAEs, mortality, and worsening of modified Rankin scores (mRS) were not different between SAC and CA. Among UIAs, SAC had a higher 1-year ischemic stroke rate (8.8% vs 2.2% p=0.005). Of note, 42% of SAC ischemic strokes occurred at one enrolling site, exclusion of which brings the comparative stroke rates to 5.1% vs 2.2%, respectively (p=0.22). There was no significant difference in ischemic stroke rates between SAC and CA within the more similar WNA subset. Angiographic outcomes. Despite a trend toward a lower rate of initial aneurysm obliteration, SAC weakly trended toward a higher rate of obliteration at 1 year in UIAs (51.8% vs 44.4%, p=0.22). Complete obliteration rates for SAC were significantly higher than CA in the WNA subset (45.7% vs 27.1%, p=0.03). Angiographic worsening was significantly lower for SAC than CA in both the UIA (16.7% vs 33.3%, p=0.002) and WNA groups (21.4% vs 50.8%, p=0.0005). Core lab analysis revealed no instances of significant stent migration at 1 year. Conclusion: SAC was safe and effective in treating unruptured intracranial aneurysms in MAPS. SAC correlated with higher coil packing densities and better angiographic outcomes at 1 year without significantly higher rates of SAEs, mortality, death or disability despite the stented aneurysms having more difficult morphology than coiled aneurysms. Ongoing clinical evaluation over the next 4 years will help assess the overall utility of the SAC approach. Competing interests: S Hetts: NIH-NIBIB, Stryker Neurovascular. Silk Road Medical. University of California. A Turk: Stryker Neurovascular. J English: Stryker Neurovascular. Silk Road Medical. J Mocco: None. C Prestigiacomo: None. G Nesbit: None. S Ge: Stryker Neurovascular. J Jin: Stryker Neurovascular. Y Murayama: Stryker Neurovascular, Asahi Intec. Inventor: Matrix Coil, Trainer: eV3, Concentric. A Gholkar: None. S Barnwell: None. D Lopes: Stryker Neurovascular. Proctor: Stryker Neurovascular. Y Gobin: None. S Johnston: Boston Scientific / Stryker Neurovascular. C McDougall: None.